PENERAPAN KRIPTOGRAFI PADA REST API WEB SERVICE STUDI KASUS KAFA PHOTOGRAPHY - Joko Christian Chandra; Irfan Irmawan (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2019)
High business competition forces businesses to adapt to the needs of increasingly complex information systems. One of the market demands is the ease of conducting transactions that are mobile but still integrated with the company's overall information system. This challenge is also faced by a small business Kafa Photography engaged in the field of photography services for public. This business requires a data access system that is secure and supports multiple interfaces. Utilizing REST web service technology that can be used as a communication bridge between different access technologies can help the intended system integration. To improve the security of business process related information, it is necessary to add a cryptographic data mechanism. This research will develop a middleware utilizing the viginere cipher cryptographic method on REST-based web service services for the Kafa Photography business venture. The results of research in the form of web service architecture which are used as connectors between different applications, namely web and mobile that support business processes. To test the functionality and compatibility of the outcome, researcher use the Postman application tool and the prototype of mobile and web applications. The effectiveness and efficiency of derivative applications that use web services to improve services for Kafa Photography customers are not measured in this study.